Ecological continuity and transformation after the Permo-Triassic mass extinction in northeastern Panthalassa. (29th March 2019) - Dineen, Ashley A.; Roopnarine, Peter D.; Fraiser, Margaret L.
Abstract : The Permo-Triassic mass extinction (PTME) is often implicated in the transition from the Paleozoic evolutionary fauna (PEF) to the modern evolutionary fauna (MEF). However, the exact timing and details of this progression are unknown, especially regarding the vacating and filling of functional ecological space after the PTME. Here, we quantify the functional diversity of middle Permian and Early Triassic marine paleocommunities in the western US to determine functional re-organization in the aftermath of the PTME. Results indicate that while the PTME was selective in nature, many new Triassic taxa either re-filled functional roles of extinct Permian taxa or performed the same functional roles as Permian survivors. Despite this functional overlap, Permian survivors and new Triassic taxa differed significantly in their relative abundances within those overlapping functions. This shift in numerical emphasis, driven by an increase in abundance towards more MEF-style traits, may represent a first step in the transition between the PEF and MEF. We therefore suggest that the extreme impact of the PTME had significant and permanent re-organizational effects on the intrinsic structure of marine ecosystems. Early Triassic ecosystems likely bridged the gap between the Paleozoic and modern evolutionary faunas, as newly originated Triassic taxa shared ecospace with Permian survivors, but shifted functional emphasis.